Multisectoral Strategies of West Java Government Protecting Women from Contract Marriage Sexual Violence Human Rights - Dadang Syaripudin; Encang Saefudin (Yayasan Lembaga Studi Makwa, 2025)
This article analyzes trends in sexual violence against women in Indonesia and West Java during 2020–2021, using structural and radical feminist theories from figures such as Sylvia Walby, Andrea Dworkin, bell hooks, Nancy Fraser, and Pierre Bourdieu. Data shows a significant increase in cases of sexual violence, including rape and harassment, dominated by perpetrators from the victim's immediate environment and exacerbated by the COVID-19 pandemic. The rape case in Cimahi is a concrete illustration of the failure of traditional protection systems for women. This research highlights the need for a multisectoral strategy and a collaborative governance model to address tradition-based violence that harms women. The West Java Provincial Government has begun implementing collaborative measures by involving service institutions, law enforcement officials, and civil society in providing protection and recovery for victims. This article recommends strengthening inclusive and gender-justice-based governance as key to preventing violence against women.